Karakteristik Tanah Yang Berkembang Dari Batuan Diorit Dan Andesit Kabupaten Sleman, Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
The research was conducted in Godean, Sleman, on soil develop from diorite, andesite parent materials. The objective of the studies are (1) to identify soil characteeristics developed from diorite and andesite rock, (2) to understand the different in mineralogical composition, weathering intensity and distribution of soil in the area under study, (3) to elaborate soil genesis. The research used methode field observation and laboratory analysis. Field observation was doing with made four soil profiles, two profiles, in soil develop from diorite rock (GW1 and GW2), one profile in soil develop from andesite rock (GBT) and the other profile in soil developed from soil transition (DV). Soil samples from each profile was analysis in laboratory. The results of research was to show soil solum relative shallow, slit/clay ratio on GW1 between